Equilibrium asset pricing in directed networks - Nicole Branger; Patrick Konermann; Christoph Meinerding; Christian Schlag (Leibniz Institute for Financial Research SAFE, 2020)
Directed links in cash flow networks a↵ect the cross-section of risk premia through three channels. In a tractable consumption-based equilibrium asset pricing model, we obtain closed-form solutions that disentangle these channels for arbitrary directed networks. First, shocks that can propagate through the economy command a higher market price of risk. Second, shock-receiving assets earn an extra premium since their valuation ratios drop upon shocks in connected assets. Third, a hedge e↵ect pushes risk premia down: when a shock propagates through the economy, an asset that is unconnected becomes relatively more attractive and its valuation ratio increases.
Keywords: G12; D85; 330; Directed cash flow networks; directed shocks; mutually exciting processes; recursive preferences